2020
DOI: 10.1080/07391102.2020.1852119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of traditional ayurvedic Kadha for prevention and management of the novel Coronavirus (SARS-CoV-2) using in silico approach

Abstract: Since the emergence of novel Coronavirus (SARS-CoV-2) infection in Wuhan, China in December 2019, it has now spread to over 205 countries. The ever-growing list of globally spread corona virus-19 disease (COVID-19) patients has demonstrated the high transmission rate among the human population. Currently, there are no FDA approved drugs or vaccines to prevent and treat the infection of the SARS-CoV-2. Considering the current state of affairs, there is an urgent unmet medical need to identify novel and effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 57 publications
0
43
0
Order By: Relevance
“…The major bioactive chemical constituents of this plant are withanolides which are chemically C 28 triterpenoid steroidal lactone and responsible for its medicinal virtue. Recently, it has also been reported that withanolides can be potentially used to cure novel coronavirus (SARS-CoV-2) as an immune booster and anti-viral agent (Maurya and Sharma 2020 ). Biosynthesis of withanolides takes place utilizing two different pathways, one is mevalonate pathway which is localized in cytosol and another is 2-C-methyl-D-erythritol-4-phosphate (MEP) pathway localized in the plastid.…”
Section: Introductionmentioning
confidence: 99%
“…The major bioactive chemical constituents of this plant are withanolides which are chemically C 28 triterpenoid steroidal lactone and responsible for its medicinal virtue. Recently, it has also been reported that withanolides can be potentially used to cure novel coronavirus (SARS-CoV-2) as an immune booster and anti-viral agent (Maurya and Sharma 2020 ). Biosynthesis of withanolides takes place utilizing two different pathways, one is mevalonate pathway which is localized in cytosol and another is 2-C-methyl-D-erythritol-4-phosphate (MEP) pathway localized in the plastid.…”
Section: Introductionmentioning
confidence: 99%
“…The decoction (known as kadha in Indian Ayurveda system) prepared from these herbs is commonly used against common cold and is suggested to be effective against COVID-19 pathogenesis. Maurya and Sharma [ 60 ] had undertaken an in silico approach to study the beneficial effect of major phytochemicals present in kadha against,SARS-CoV-2. Further, Gautam and coworkers [ 61 ] reported that such herbal decoction possessed significant anti-viral and immunomodulatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…An array of phytochemicals has been found to have significant docking scores and potential to inhibit different stages of SARS-CoV-2 infection as well as significant anti-inflammatory property. The authors claim that study provides evidence of the binding of active ingredients present in different plants used in Kadha preparation with viral proteins and target proteins for prevention and treatment of the COVID-19 [25].…”
Section: Discussionmentioning
confidence: 99%